ESTUDOS SOBRE EL FLUTTER Y LA FIBRILLATION III LA ACTIVIDAD AUTOSOSTENIDA EN EL MUSCULO AURICULAR AISLADO DEL MAMIFERO - ROSENBLUETH, ARTURO; GARCIA RAMOS, J (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
22 rabbits were given intraven injns of alloxan (170-240 mg, per kg) Intramusc injns of epinephrine in doses of 200 micrograms- per kg 60-80 min before admn of alloxan markedly hindered or abolished the diabetogenic effect of alloxan in most case
ASTRON J
Keywords: ESTUDOS, FLUTTER, FIBRILLATION, ACTIVIDAD AUTOSOSTENIDA, MUSCULO AURICULAR AISLADO, MAMIFERO; CIENCIAS DE LA VIDA; FISIOLOGIA HUMANA; FISIOLOGIA CARDIOVASCULAR